The Effects Of Serıal Extractıon On The Soft-Tıssue Profıle - Lale Sarısoy; Hakan N. İşcan; Şenol Sarısoy (Galenos Yayinevi, 1998)
Serial extraction has been said to lead to straight profiles due to the extraction of premolars. Contrary opinions declaring that premolar extraction does not cause undesirable flattening of the facial profile are also present. This study was done in order to determine the effects of serial extraction on the facial profile. A serial extraction group consisting of 20 patients and a control group of 21 cases with Angle Class I and slight Class II, I malocclusions were constructed. These groups were matched according to their age and vertical and sagittal skeletal cephalometric characteristics. The serial extraction procedure was carried out according to Dewel and the control group was followed for 3 to 5 years without any orthodontic treatment. The results of this study do not support the claim that serial extraction has deleterious effects on the soft tissue profile. No other apparent effect of serial extraction on the soft tissue profile were observed, other than those on the soft tissue B point and thereby on the labiomental angle.